2021
DOI: 10.3390/jcm10040719
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetics and Recurrence after Cancer Surgery-What’s New? A Narrative Review

Abstract: The perioperative use of regional anesthesia and local anesthetics is part of almost every anesthesiologist’s daily clinical practice. Retrospective analyses and results from experimental studies pointed towards a potential beneficial effect of the local anesthetics regarding outcome—i.e., overall and/or recurrence-free survival—in patients undergoing cancer surgery. The perioperative period, where the anesthesiologist is responsible for the patients, might be crucial for the further course of the disease, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 129 publications
0
12
0
Order By: Relevance
“…The impact of local anesthetics on cancer and its recurrence after surgery has spurred a wave of interest over the last decade. Two recent reviews covering this field have been published (132,133). In the present article we attempted to synthesize the current preclinical and clinical state of the art, while evoking the capacity of local anesthetics to stimulate anticancer immune responses, thereby potentiating the efficacy conventional anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of local anesthetics on cancer and its recurrence after surgery has spurred a wave of interest over the last decade. Two recent reviews covering this field have been published (132,133). In the present article we attempted to synthesize the current preclinical and clinical state of the art, while evoking the capacity of local anesthetics to stimulate anticancer immune responses, thereby potentiating the efficacy conventional anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical investigations showed that malignant cells are shed into the bloodstream during surgical manipulation of a primary tumor, leading to an increased incidence of distant metastases [ 21 , 23 ]. As outlined above, regional anesthesia might be able to reduce the stress response induced by surgery and also preserve NK cells activity as one of the most important factors for the elimination of CTC [ 24 ]. We noted a significant difference in CTC counts when combined and general anesthesia groups were compared.…”
Section: Discussionmentioning
confidence: 99%
“…The perioperative use of anesthesia forms a crucial part of daily clinical practice in patients undergoing surgery. In cancer surgery, the perioperative period constitutes an important stage for the further course of the disease, as circulating tumor cells shed from the primary tumor into the patient’s bloodstream might form new micro-metastases independent of complete tumor removal ( 6 ). Various studies have investigated the potential beneficial effect or otherwise of the different anesthesia techniques regarding outcome (overall and/or recurrence-free survival) in patients undergoing cancer surgery.…”
Section: Anesthesia In Cancer Patientsmentioning
confidence: 99%
“…Local anesthetics may exert a certain degree of influence on circulating tumor cells shed during surgery through direct or indirect means because of their strong anti-inflammatory properties. For example, they could contribute to blunting the inflammatory stress response induced by the surgical stimulus ( 6 ).…”
Section: Anesthesia In Cancer Patientsmentioning
confidence: 99%